Raining on Rainbows: A Comparative Study Of LGBT Anti-Discrimination Ordinances Between the Local Governments of Marikina, Manila, and Mandaluyong in the Philippines - Arizabal, Francia Denise; Aspa, Ashley Vocae; Manalo, Jazztin Jairum (Universitas Muhammadiyah Tangerang, 2023)
The study is drawn from the challenges and experiences of the LGBT individuals in the country experiencing discrimination and harassment due to marginalization which remained to create barriers to equality for LGBT people. The passing of Anti-Discrimination Ordinances in selected cities in Metro Manila is a triumph for many LGBT groups. The study shed light on comparison of Anti-Discrimination Ordinances and the existing LGBT ordinances between the selected local governments of Metro Manila in terms of its implementation and effects. It identified which among the local government units (LGUS) initiatives suits to be the best that may serve as model for other local governments in their future legislation of their own Anti-Discrimination Ordinance. The study utilized the Principal-Agent Theory to contextualize a situation in which local governments are involved. A qualitative comparative analysis that used key informant interviews and surveys is utilized in the study. Results presented that despite having the same composition and provisions when it comes to its enactment, Marikina, Manila, and Mandaluyong differ in ways and use of systems in terms of enforcement. Thus, the three LGUs may further establish mechanisms to monitor complaints of gender-based violence and provide guidelines in handling LGBT victims and may incorporate awareness-raising campaigns. Studi ini diambil dari tantangan dan pengalaman individu LGBT di negara tersebut yang mengalami diskriminasi dan pelecehan karena marginalisasi yang tetap menciptakan hambatan kesetaraan bagi orang-orang LGBT. Pengesahan Undang-Undang Anti-Diskriminasi di kota-kota terpilih di Metro Manila adalah kemenangan bagi banyak kelompok LGBT. Studi ini menjelaskan perbandingan Undang-Undang Anti-Diskriminasi dan peraturan LGBT yang ada antara pemerintah daerah Metro Manila yang dipilih dalam hal implementasi dan efeknya. Ini mengidentifikasi inisiatif mana di antara unit pemerintah daerah (LGUS) yang cocok untuk menjadi yang terbaik yang dapat berfungsi sebagai model bagi pemerintah daerah lainnya dalam undang-undang masa depan mereka tentang Undang-Undang Anti-Diskriminasi mereka sendiri. Penelitian ini menggunakan Teori Principal-Agent untuk mengontekstualisasikan situasi di mana pemerintah daerah terlibat. Analisis komparatif kualitatif yang menggunakan wawancara dan survei informan kunci digunakan dalam penelitian ini. Results mempresentasikan bahwa meskipun memiliki komposisi dan ketentuan yang sama dalam hal pemberlakuannya, Marikina, Manila, dan Mandaluyong berbeda dalam cara dan penggunaan sistem dalam hal penegakan hukum. Dengan demikian, ketiga LGUS tersebut selanjutnya dapat membangun mekanisme untuk memantau pengaduan kekerasan berbasis gender dan memberikan panduan dalam menangani korban LGBT dan dapat menggabungkan kampanye peningkatan kesadaran.